Effects of Red Rosela Tea (Hibiscus sabdariffa) as An Organic Inhibitor for Low Carbon Steel in An Environment of Sodium Chloride 3,5% - Giafin Bibsy Rahmaulita; Johny Wahyuadi Mudaryoto Soedarsono (Recent in Engineering Science and Technology, 2025)
Corrosion is an unavoidable phenomenon that is commonly observed in everyday life, particularly in infrastructure and tools constructed from low carbon steel. The corrosion of low carbon steel in chloride-rich environments presents a critical issue across numerous industrial sectors. One widely adopted method for mitigating corrosion involves the application of corrosion inhibitors, chemical substances that even in small concentrations, can significantly suppress the rate of metal degradation in corrosive environments. This research examines the potential of red roselle extract (Hibiscus sabdariffa) as a green corrosion inhibitor for low carbon steel in a 3.5% sodium chloride solution. The corrosion inhibition performance will be evaluated based on weight loss measurements over varying exposure periods of 3, 6, 9, and 12 days. Red roselle tea concentration of 10 g/L will be utilized, supplemented with an additional 2 mL of liquid inhibitor. The results of this study indicate that the maximum corrosion inhibition efficiency reaches 16% after 9 days of immersion, while the lowest efficiency is observed at 8% after 3 days. pH measurements and corrosion potential analysis suggest that red roselle tea contributes to reducing the corrosion rate by forming a protective layer on the surface of low carbon steel.